Measurement of apolipoprotein B concentration in plasma lipoproteins by combining selective precipitation and mass spectrometry - Laurent Beghin; Nathalie Duhal; Philippe Poulain; Philippe Hauw; Brigitte Lacroix; Jean-Michel Lecerf; Jean-Paul Bonte; Jean-Charles Fruchart; Gérald Luc (Journal of Lipid Research, 2000)
The measurement of apolipoprotein B (apoB) in purified lipoproteins by immunological assays is subject to criticism because of denatured epitopes or immunoreactivity differences between purified lipoproteins and standard. Chemical methods have therefore been developed, such as the selective precipitation of apoB followed by quantification of the precipitate. In this study, we present the measurement of apoB concentration in lipoproteins purified by ultracentrifugation by combining isopropanol precipitation and gas chromatography/mass spectrometry. Very low density lipoprotein (VLDL; d < 1.006 g/mL); VLDL plus intermediate density lipoprotein (VLDL + IDL; d < 1.019 g/mL); and VLDL, IDL, and low density lipoprotein (VLDL + IDL + LDL; d < 1.063 g/mL) were purified by ultracentrifugation. Apolipoprotein B-100 was selectively precipitated by isopropanol. The leucine content of the pellet was then determined by gas chromatography/mass spectrometry, using norleucine as internal standard. Knowledge of the number of leucine molecules in one apoB-100 molecule makes it possible to calculate the plasma concentration of apoB in the various lipoprotein fractions. ApoB in IDL (d 1.006–1.019 g/mL) and LDL (d 1.019–1.063 g/mL) were then determined by subtracting VLDL-apoB from apoB in lipoproteins d < 1.019 and apoB in lipoproteins d < 1.019 g/mL from apoB in lipoproteins d < 1.063 g/mL, respectively. The isopropanol precipitate was verified as pure apoB (>97%) in lipoprotein fractions isolated from normo- and hyperlipidemic plasma and the method appeared reproducible.The combination of isopropanol precipitation and the GC/MS method appears therefore to be a precise and reliable method for kinetic and epidemiological studies.